Gene Annotation in High Schools: Successful Student Pipeline and Teacher Professional Development in Bioscience Using GENI-ACT - Koury, Stephen T.; Carlin-Menter, Shannon; Dey-Rao, Rama; Kelly, Kimberle (Frontiers in Microbiology, 2021)
Knowledge of genomics is an essential component of science and health literacy for high school students, however few high school teachers have received genomics training or any guidance on how to teach the subject to their students. This project explored the impact of a genomics and bioinformatics research pipeline for high school teachers and students using an introduction to genome annotation research as the catalyst. The Western New York-based project had three major components: 1) a summer teacher professional development workshop to introduce genome annotation research, 2) teacher-guided student genome annotation group projects during the school year, 3) with an end of the academic year capstone symposium to showcase student work in a poster session. Both teachers and students performed manual gene annotations using an online annotation toolkit known as GENI-ACT, originally developed for use in a college undergraduate teaching environment. During the school year, students were asked to evaluate the data they had collected, formulate a hypothesis about the correctness of the computer pipeline annotation, and present the data to support their conclusions in poster form at the symposium. Evaluation of the project documented increased content knowledge in basic genomics and bioinformatics as well as increased confidence in using tools and the scientific process using GENI-ACT, thus demonstrating that high school students are capable of using the same tools as scientists to conduct a real-world research task.